LEGAL CERTAINTY AND DISTRIBUTIVE JUSTICE IN THE AGE LIMITATION OF NOTARY OFFICE TENURE FOLLOWING CONSTITUTIONAL COURT DECISION NUMBER 84/PUU-XXII/2024 - hamler hamler; Khairul Azwar Anas; Ferry Asril; Tat Marlina; Martha Hasanah Rustam; Hawa Raissa Agripina (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
Constitutional Court Decision Number 84/PUU-XXII/2024 constitutes a constitutional milestone in the judicial review of Article 8 paragraph (2) of Law Number 30 of 2004 concerning the Office of Notary, which regulates the extension of a notary's term of office up to the age of 67 years subject to the notary's health condition. The Panel of Constitutional Court Justices partially granted the petition and declared the provision contrary to the 1945 Constitution of the Republic of Indonesia, particularly Article 28D paragraph (1) concerning the right to legal protection and fair legal certainty. This study aims to: (1) identify and analyze the legal reasoning of the Constitutional Court in the aforementioned decision; (2) examine its implications for the fulfillment of the principle of distributive justice between the continued professional practice of senior notaries and the regeneration of younger notaries; and (3) assess the reconstruction of regulations governing the notarial profession following the decision in order to provide fair legal certainty and strengthen the notarial institution in Indonesia. This research employs a normative legal research method using statutory, case, and conceptual approaches. Data were collected through document studies of relevant legislation, Constitutional Court decisions, theories of distributive justice, and academic literature, and were subsequently analyzed using a descriptive-qualitative method. The findings indicate that the Constitutional Court determined that the term of office of a notary may be extended until the age of 70 years, subject to annual medical examinations conducted at a central government hospital, a regional public hospital, or a hospital designated by the Minister responsible for legal affairs. In reaching this conclusion, the Court set aside the principle of the open legal policy doctrine on the grounds that the challenged provision contained irrationality and intolerable injustice. Regulatory reconstruction is therefore necessary to ensure that professional protection balances the interests of senior notaries with the need for professional regeneration, while simultaneously strengthening legal certainty in the sustainable administration of Indonesia’s notarial institution.